(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To determine the features of the untrastructural reorganization in the rat retina by the end of week 4 and week 6 of experimental opioid exposure. Material and Methods: Forty-eight adult male albino rats (weight, 200-250 g; age, 4.5 months) were used in this study. They received nalbuphine hydrochloride intramuscularly daily for 42 days. Particularly, the drug was administered daily at a dose of 0.212 mg/kg for weeks 1 and 2, 0.225 mg/kg for weeks 3 and 4, and 0.252 mg/kg for weeks 5 and 6. In this way, we experimentally created the conditions of chronic opioid exposure. Animals were divided into three groups. Group 1 (19 animals) received nalbuphine for 28 days, and group 2 (19 animals), for 42 days. Group 3 (control group) comprised 10 animals. Of these, 5 animals were treated with normal saline at a dose of 0.22 mg/kg intramuscularly daily for 28 days, and the rest were treated in a similar manner for 42 days. Transmission electron microscopy studies of the rat retina were conducted in a routine manner. Results: By the end of week 4 of experimental opioid exposure, there was an increase in the number of retinal microvessels with signs of hyperemia and degenerative changes in retinal pigment epithelium (RPE) cells, increase in the destruction of membranous discs of photoreceptor outer segments, necrobiotic changes in the nuclei of individual photoreceptors, axonal degeneration in the outer and inner plexiform layers, degenerative changes in retinal horizontal neurons, and the appearance of necrotic structural changes in the cytoplasm of bipolar and amacrine cells. By the end of week 6, there was a further increase in hyperemia of retinal vessels and degenerative and necrotic changes in individual RPE cells and photoreceptor outer segments. In addition, we observed destruction and shortening of mitochondrial cristae of photoreceptor inner segments, necrotic nuclear changes in individual photoreceptors, degeneration of axons of the outer and inner plexiform layers, degenerative and necrotic changes in bipolar and amacrine cells, hypertrophic Müller cell processes, degeneration of ganglion cells, and vascular hyperemia and moderate perivascular edema in the outer and inner plexiform layers. Conclusion: Therefore, in the current rat study, after a 4-week exposure to daily nalbuphine injections at a dose ranging 0.212 to 0.253 mg/kg, there was ultrastuctural evidence of destructive processes in the RPE and photoreceptor outer segments, axonal degeneration in the outer and inner plexiform layers, degenerative and necrotic changes in bipolar and amacrine cells, hypertrophic Müller cell processes, ganglion cell degeneration and hyperemia due to an impaired retinal microcirculatory ultrastructure. At week 6 of the experiment, there was evidence of increased destructive and degenerative processes in structural components of the retina.